New Generalization of -Best Simultaneous Approximation in Topological Vector Spaces - Mahmoud Rawashdeh; Sarah Khalil (Abstract and Applied Analysis)
Let be a nonempty subset of a Hausdorff topological vector space , and let be a real-valued continuous function on . If for each , there exists such that , then is called -simultaneously proximal and is called -best simultaneous approximation for in . In this paper, we study the problem of -simultaneous approximation for a vector subspace in . Some other results regarding -simultaneous approximation in quotient space are presented.